Nilai Perusahaan: Telaah Kebijakan Dividen, Ukuran Perusahaan, Likuiditas dan Profitabilitas - Intan Kusumawati Cahyaningrum; Shinta Permata Sari (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The firm value represents a certain status achieved by the company as a sign of public trust to the company after carrying out its operations for several years, from its establishment up to the present time. This study aims to examine the effect of Dividend Policy, Firm Size, Liquidity, and Profitability on Firm Value in companies within the basic material sector listed on the Indonesia Stock Exchange (IDX) during the 2022–2024 period. This study applies a quantitative approach with secondary data obtained from annual reports and audited financial statements published on the IDX website and the respective companies. Sampling was conducted using a purposive sampling technique, resulting in 30 companies or 90 data observations. Data analysis is conducted using multiple linear regression. The results indicate that dividend policy, company size, liquidity, and profitability effect firm value.